Investigation on the Psychological Status and Influencing Factors of Medical Staff in Fever Clinics under the Context of Normalized Epidemic Prevention and Control in Taishan City - Liu, Yuchang; He, Junchu (Pacific International Journal, 2024)
To explore the psychological condition of medical personnel in fever clinic in Taishan City under the background of normalized epidemic prevention and control, and to analyze the related influencing factors. The medical staff of fever outpatient clinics in 24 medical institutions in Taishan City under the prevention and control of the normalized COVID-19 outbreak were selected as the study subjects,using the whole-population sampling method. The psychological status of the medical staff of the fever outpatient clinics and their influencing factors were analyzed by using statistical methods such as multiple linear regression, with the Self-rating Scale of Mental Health Symptoms, the Stress Perception Scale, and the Family Apathy Index. In the study,a total of 422 questionnaires were collected with a validity rate of 82.46%. Person correlation results showed that stress feeling score was positively correlated with SCL-90 score (r<0.60), and family caring was negatively correlated with SCL-90 score (r<-0.30). Multiple linear regression models showed that respondents had difficulty in falling asleep (b=8.96), early awakening (b=9.07), humanistic care in hospitals (b=6.82), feelings of stress (b=2.29), and family caringness score (b=-1.34), were linearly correlated with the mental health status of medical staff. Medical staff of fever clinics in Taishan City in the context of normalised epidemic prevention and control are still in a highly stressful working environment, resulting in such situations as reduced sleep quality and deteriorated psychological conditions. Hospital management should make effort to provide sufficient humanistic care and sleep guidance for medical staff in fever clinics.